Primary sleep apnoea syndrome. Issue 11 (November 1981) - Chokroverty, S; Sharp, J T
Abstract : Polygraphic study in 18 men with the sleep apnoea syndrome showed central, upper airway obstructive, and mixed apnoeas. Fifty per cent of the total apnoea time was central, 33% was obstructive, and 17% was mixed. Apnoeic episodes were accompanied by oxygen desaturation, relative bradycardia and hypotonia of orofacial muscles innervated by ponto-medullary neurons. During regular breathing these muscles revealed tonic and phasic inspiratory EMG activities. The data suggest that the primary sleep apnoea syndrome results from a dysfunction of the central control of breathing.